2004
DOI: 10.1002/ar.a.20062
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of apoptosis during normal cloacal development in mice

Abstract: To understand normal cloacal developmental processes, serial sagittal sections of mouse embryos were made every 6 hrs from embryonic day 11.5 (E11.5) to E13.5. During cloacal development to form the urogenital sinus and anorectal canal, fusion of the urorectal septum with the cloacal membrane was not observed, and the ventral and dorsal parts of the cloaca were continuously connected by the canal until disappearance of the cloacal membrane to open the vestibule formed by the urogenital sinus and anorectal cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 40 publications
7
56
0
1
Order By: Relevance
“…Recently, Sasaki et al (2004) and Yamaguchi et al (2008), studying mouse embryos, demonstrated an intimate topographical relationship between the bulbospongiosus and the EAS promordium. Valasek et al (2005), using chick and mouse embryos, confirmed experimentally that all perineal muscles including the EAS are derived from the ventral muscle mass of the hind limb.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sasaki et al (2004) and Yamaguchi et al (2008), studying mouse embryos, demonstrated an intimate topographical relationship between the bulbospongiosus and the EAS promordium. Valasek et al (2005), using chick and mouse embryos, confirmed experimentally that all perineal muscles including the EAS are derived from the ventral muscle mass of the hind limb.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how ARMS develop requires a knowledge of how the urorectal area normally develops; however, the mechanism by which the mammalian cloaca forms the urorectal sinus and anal canal is still a contentious issue (Sasaki et al, 2004a). The external development of zebrafish embryos allows the urorectal area to be examined in vivo as it matures.…”
Section: Discussionmentioning
confidence: 99%
“…1C,H and Fig. 2C; Nievelstein et al, 1998;Perriton et al, 2002;Sasaki et al, 2004;Seifert et al, 2008Seifert et al, , 2009aLin et al, 2009;Ng et al, 2014;Ching et al, 2014;Miyagawa et al, 2014).…”
Section: Introductionunclassified